A Design of Experiment-based Approach for the Formulation Development and Evaluation of Repaglinide Transdermal Patch Using Natural Polymers (Asian Journal of Pharmaceutics (AJP), 2022)
Aim: The main aim of this study was to Formulation and Characterization of Repaglinide Transdermal Patch UsingNatural polymers. Materials and Methods: The Box–Behnken design was used, which has three levels and threefactors to investigate the associate impact of significant attributes on tensile strength, In vitro drug release, and Exvivo drug permeation. Fifteen formulations were developed that differed in the polymer ratio (9:1, 8:1, and 7:1).The permeation of repaglinide through hairless goat ear skin through Ex vivo was found to increase with the helpof permeation enhancer d-limonene. Results: As per the experimental data, it is concluded that the R12 is the bestformulation in ex vivo permeation, in which we have taken 30% propylene glycol as a plasticizer, 3% d-limoneneas a permeation enhancer, and this formulation shown 301.825 μg/cm2 permeation in 24 h. Conclusion: Afteroptimizing all formulations, it concluded that the ratio of polymer in 9:1, 3% of a permeation enhancer, and 30%plasticize was the optimum quantity of different excipients used in the optimized formulation. These findingssuggest that transdermal repaglinide delivery may have therapeutic promise, with benefits such as reduced dosefrequency, better patient compliance, non-invasive properties, enhanced bioavailability, and ease of medicationdiscontinuation.